(untitled) (LEARNing Landscapes, 2019)
We explore how valuing Black male students’ literacies within academic contexts during multimodal writing can position students’ ways of knowing at the center of their learning. This centering requires a repositioning of students’ cultural literacies at the core of instruction. Using multiliteracies and Critical Discourse Analysis frameworks, we analyze and share excerpts from conversations with three Black adolescent high school seniors as they composed and reflected upon authoring digital autobiographies for an assignment in their Black Literature class. These reflections illuminate how the students drew on culturally salient texts to share elements of themselves with their peer and teacher audience.